Perbandingan Hasil Radiograf pada Pemeriksaan Lumbosacral Antero Posterior Menggunakan Grid dan Tanpa Grid - Wahyuddin, Wahyuddin; Iskandar, A.AR. Rakhmansya; Kusuma, Ahmad Pramudya Ramadhana (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2023)
The grid is an inspection tool that is used to absorb scattered radiation that is not directional from the object being exposed. Routine projections on lumbosacral examination are posterior (AP) and lateral Antero projections. This study was conducted to determine the comparison of the radiographs of the lumbosacral examination using a grid and without a grid. This type of research is qualitative research with a descriptive approach. The samples taken in this study were 2 samples with lumbosacral examination patients. Data collection was obtained from the method of observation, questionnaires, and documentation. Based on the research that has been done, the lumbosacral examination using the grid produces a better picture than the image that does not use a grid.